Honey dressing as a means of granulation tissue promoter for wounds in patients with diabetic foot ulcers - Sadagatullah, Abdul Nawfar (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Honey has been used as dressing material for various types of wound.The orthopaedic department of the school of Medical sciences , Un1versiti Sains Malaysia have experience using honey on recalcitrant wound at the foot of diabetic patients. An anecdotal observation is the promotion of healing has been hastened in these types of wound.Worldwide, similar finding have been noted with various types of wound treated with honey dressing. The New Zealand 'Manuka' Honey has been extensively studied and is claimed to have superior chemical desloughing properties and also as a .good agent for promotion of granulationThe 'Manuka' honey from New Zealand is at present being promoted and being sold as a medical product for wound dressing with substantial research to back the manufacturers' claims At present the local Tualang Honey has been discovered to be consistent in its content and has a potential to be promoted as 'medical grade' honey. This study was part of a group of studies done by the honey research cluster/ group. It was a head to head randomized single blinded clinical trial comparing the granulation tissue promoting effects of Tualang Honey as compared to the gold standard widely acclaimed Manuka honey. The general objective was to prove that the malaysian Tualang honey was comparable to Manuka honey to treat recalcitrant wounds (the example wound chosen was a diabetic foot ulcer). The study aim is so that at one time the Malaysian honey can be marketed as medical grade honey.